Expression of thrombospondin-1 and its receptor CD36 in human osteoarthritic cartilage. Issue 6 (1st June 2000) - Pfander, David; Cramer, Thorsten; Deuerling, Dieter; Weseloh, Gerd; Swoboda, Bernd
Abstract : OBJECTIVE: Thrombospondin-1 (TSP-1), a trimeric glycoprotein, is involved in cell-matrix interactions of various tissues, particularly in cartilage. Biochemical analyses show expression of TSP-1 in human cartilage, but its cellular source as well as the presence of its main surface receptors CD36 and CD51 in normal and osteoarthritic cartilage remain unknown. Therefore, to localise TSP-1 and its receptors immunohistochemistry and in situ hybridisation were used. METHODS: Radioactive in situ hybridisations with an RNA probe that encodes TSP-1 combined with immunostaining were carried out to investigate the expression patterns of TSP-1, CD36, and CD51 in seven normal and 23 osteoarthritic human cartilage samples. RESULTS: In normal cartilage TSP-1 was present mainly in the middle and upper deep zone. RNA expression was predominantly seen over chondrocytes of the middle zone. CD36 was found in chondrocytes of the superficial and upper middle zone. In mild and moderate osteoarthritic cartilage an increased number of TSP-1 expressing chondrocytes were seen and an increased pericellular staining close to the surface. In severe osteoarthritic cartilage a decrease in the number of TSP-1 synthesising chondrocytes and a strong reduction in matrix staining were observed. Most of these severe osteoarthritic samples showed a strongly enhanced number of CD36 positive chondrocytes. CONCLUSION: The cellular source of TSP-1 in normal cartilage is mainly mid-zone chondrocytes, which also express CD36. In early osteoarthritic cartilage lesions an increase of TSP-1 was seen, whereas reduced TSP-1 synthesis is paralleled by a strong decrease in TSP-1 protein staining in severe osteoarthritis. Furthermore, in severe osteoarthritic cartilage the number of CD36 immunostained chondrocytes is significantly increased.